ANALISIS SOSIAL-EKONOMI RUMAH TANGGA PEKERJA AGROINDUSTRI ROTAN DI KOTA PEKANBARU (Economy and Social Analysis of the Worker Household of Rattan Agroindustry in Pekanbaru City) - A Z Fachri Yasin; Djaimi '; Elinur ' (JIP ( Jurnal Industri dan Perkotaan ), 2005)
The purpose of this research is to analyze the factor which influence time workallocation, income and the worker household expenseas and then to analyze characteristicwork variety influence for economic decision making of the worker household. The resultestimate economy model of the worker household concluded that the internal factors whichinfluence time work allocation in worker household but not responsive is work generationtotal, work experience and worker age. Time work allocation of worker household as notresponsive for the worker household income internal and external work.The worker householdincome responsive for work expression of worker household in work, that is not responsivefor internal factors work experience and work generation total of the worker household. Allexpenseas of the worker household is influence by positive and responsive for total incomeof the worker household, except food consumtion expenseas not responsive. Educationinvestment of the worker household also responsive for school child. Then, capabilityincreasing work experience the worker household by internal and external work, daily fee kindvariety to appoint wholesale and positive influential combination to worker householdeconomy.